El español en la red, desde América Latina - MORALES CAMPOS, Estela (Revista General de Información y Documentación, 2010)
Undoubtedly, the Spanish language has become nowadays a factor not only encouraging communication, but also the intercultural harmonious coexistence in Latin America. On its part, migration, among other phenomena, has been favoring the internationalization of our language in no Spanish speaking regions. Therefore, while the Spanish language is used in technological, social and cultural interchanges, it may enter to the cultural product international market in those areas. Upon performing searches in Spanish in the web on subjects relevant for Latin America, we found numerous occurrences; in turn, in the representative data base statistics, searches from different countries are registered. Likewise, such subjects are represented in the Web in other languages, with documents written by Latin American people themselves or by interested people living in other countries and speaking other languages.In order that the information in Spanish be visible and representative in the Web, besides being registered, it must be of easy access; these actions shall always require the participation of authors, editors, technologists, readers, bibliothecologists, and politicians.
Keywords: Spanish language; Internet; Electronic information; Latin America; Information Society; Intercultural communication; Information diversity